Towards an existential phenomenological interpretation of C.G. Jung's analytical psychology - Brooke, Roger, 1953- (Rhodes University, Faculty of Humanities, Department of Psychology, 1989)
The central aim of this study was to interpret the psychology of C.G . Jung in the light of existential phenomenology, thereby to lay the foundations for an integrated phenomenological analytical psychology. It was recognised that although Jung introduced a poetic understanding of psychological life he tended to adhere theoretically to a Cartesian and natural scientific epistemology and ontology, in which the knower is separated from the known, and psychological life is encapsulated inside the human subject. Thus the main task, which defined generally the study's scope and limitations, was to undercut the lingering Cartesianism in Jung's thought, thereby to recover the world in which one lives as intrinsically and authentically psychological, and one's psychological life as irreducibly world-related. The ontological guidelines for this endeavour were taken primarily from Heidegger and Merleau-Ponty, but it was consistently argued that this hermeneutic movement towards an existential understanding is given within Jung's work itself. Thus: Jung's method is primarily hermeneutic-phenomenological; the psyche is not "mind" or an inner realm more or less linked to the body, but is the embodied life-world, and Jung's descriptions of it - of its autonomy, spatiality and bodiliness, for instance - achieve ontological clarity when it is articulated as Dasein; the self as the totality of the psyche is interpretated in terms of Dasein, and individuation involves differentiation, personalisation and appropriation within existence itself; the complexes, archetypally grounded, are the vital densities of incarnate life, ambiguously conscious and unconscious, known and lived; the archetypes are the fundamental necessities of psychological life, autonomous imaginal structures within which both body and world are founded. Imaginal autonomy is revealed ontically as the metaphorical reality of things, but since imaginal autonomy has no ground thought about psychological life is ultimately poetic. Where relevant, recent theoretical developments in analytical psychology were discussed, particularly the Developmental and Archetypal movements. A clinical study was presented to illustrate some of the main themes of the thesis. In conclusion, the main themes of an integrated phenomenological analytical psychology were outlined, and the central contributions of analytical psychology and existential phenomenology were highlighted.
Keywords: Jung, C G (Carl Gustav), 1875-1961; Existential phenomenology; Phenomenology; Psychoanalysis; Psychology